2-(4-Acetamidophenoxy)-2-methylpropanoic acid - Navarrete-Vázquez, Gabriel (International Union of Crystallography, 2013)
In the title compound, C(12)H(15)NO(4), the dihedral angle between the acetamide group and the ring is 29.6 (2)(su?)°. In the crystal molecules are linked through N—H⋯O and O—H⋯O hydrogen bonds, thereby forming corrugated sheets propagating in the ac plane. These sheets are composed of R (4) (4)(28) graph-set motifs.